Association of deliberate Self Harm among patients with Bipolar Disorder in Karachi - Laraib Khan, Sameera Ali Rizvi, Washdev Amar, Zubair Ali Channa, Javeria Akhter (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the association of suicide attempt among bipolar disorder patients and evaluate the associated risk factors. Methodology: The target population of the study was adult psychiatric patients who visited the outpatient department of an institute of behavioral sciences in Karachi. A case-control study was conducted in the outpatient department of two major psychiatric services in Karachi. Participants of age above 15 years were recruited through non-purposive sampling and data was collected by a structured questionnaire. Results: From January to April 2021, of the 146 selected psychiatric patientsa, high prevalence of suicide attempts was observed in patients with young age between 20 to 30 years (p=0.000) Almost41.1%of participants were illiterate and 63% belonged to low socioeconomic status) Approximately 43.8% (p=0.00) cases had a history of mental trauma and 24.7% 76.7% (p=0.007) cases had a family history of suicide. It was found that 91.8% (p=0.00) of depression was related to suicide attempt the factors associated with suicide attempt were females, young age, illiteracy, lower socioeconomic status, presence of bipolar disorder, substance abuse, mental trauma, depression, family history of suicide and self-harm. Conclusion: We conclude that there is an association between suicide attempts and bipolar disorder. Mental illnesses are becoming an emerging public health problem. Deeper research into the relationship between suicide attempts and substance abuse, or family history and awareness in psychiatric patients is needed.